Respuesta :
First, determine the slope of the radius by the equation,
m = (y₂ - y₁)/ (x₂ - x₁)
Substituting the known values,
m = (1 - -2)/(8 - 4) = 3/4
If the unknown line is perpendicular to this, the slope should be the negative reciprocal which is equal to -4/3. Using the point-slope form to determine the equation,
y - y₁ = m(x - x₁)
Substituting the known values,
y - -2 = (-4/3)(x - 4)
Simplifying,
y + 2 = (-4/3)(x - 4)
3y + 6 = -4x + 16
Answer: 4x + 3y = 10
m = (y₂ - y₁)/ (x₂ - x₁)
Substituting the known values,
m = (1 - -2)/(8 - 4) = 3/4
If the unknown line is perpendicular to this, the slope should be the negative reciprocal which is equal to -4/3. Using the point-slope form to determine the equation,
y - y₁ = m(x - x₁)
Substituting the known values,
y - -2 = (-4/3)(x - 4)
Simplifying,
y + 2 = (-4/3)(x - 4)
3y + 6 = -4x + 16
Answer: 4x + 3y = 10
Answer:
[tex]y[/tex]= -[tex]\frac{4}{3}[/tex][tex]x[/tex][tex]+[/tex][tex]\frac{10}{3}[/tex]
Step-by-step explanation:
Otras preguntas
Which shows a perfect square trinomial?
50y2 – 4x2
100 – 36x2y2
16x2 + 24xy + 9y2
49x2 – 70xy + 10y2
Who promises to "raise (Juliet's) statue in pure gold" a. Capulet b. the Prince c. Romeo d. Montague